Tendência na incidência da febre chikungunya durante a pandemia do COVID-19 no Nordeste brasileiro - Silva, Jonathan David Biu da (2023)
Introduction: CHIKV is an arbovirus transmitted by mosquitoes of the Aedes family, its signs and symptoms are similar to other arboviruses, with its striking characteristic being symmetrical polyarthalgia. The diagnosis is made based on clinical signs and through blood testing. The virus transmission period is longer during rainy periods due to the vector's life cycle. On the other hand, Brazil went through a pandemic at the same time as Covid-19, its clinical signs are often very similar to those of arboviruses, which can lead to erroneous diagnoses, but Covid-19 has a greater respiratory characteristic. The objective of this study was to analyze temporal trends in the incidence of chikungunya fever during the COVID-19 pandemic in northeastern Brazil. Method: This is a descriptive, ecological study of time series analysis, through the anal-ysis of computerized secondary data from the Information Technology Department of the Uni-fied Health System (DATASUS), in addition to notification forms through the SINAN online notification and health problems system. /Web. Data was extracted and the Joinpoint regression model was chosen to analyze CHIKV infection rate trends during the COVID-19 pandemic. Results: Among the findings, a decrease in the number of cases was observed in 2020, with evolution and growth in 2022, a period that can be traced back to the beginning and end of the covid-19 pandemic. Furthermore, the results showed a higher incidence rate in the months of March-June. Conclusions: CHIKV is not directly related to the covid-19 virus, however some similar symptoms can lead to diagnostic errors, since with the active pandemic period attention has turned to this disease. Furthermore, this study shows us the difficulty of testing, since the incidence rate in the population is low, but the reality in terms of the number of hospitalizations and sequelae of chikungunya fever does not match the reported quantity.